Fabrication of a polymer brush-functionalized porphyrin-based covalent organic framework for enrichment of N-glycopeptides - Wang, Bing; Zhang, Xiaoya; Hua, Shuwen; Ding, Chuan-Fan; Yan, Yinghua (Mikrochimica acta (1966), 2024)
A surface-initiated atom transfer radical polymerization method combining click chemistry was employed to prepare a novel porphyrin-based covalent organic framework composite grafted with polymer brushes (TAPBB@GMA@AMA@Cys) for the specific enrichment of N-glycopeptides. The material successfully realized the high efficiency enrichment of N-glycopeptides with good selectivity (1:1000), low detection limit (0.2 fmol/μL), and high loading capacity (133.3 mg·g −1 ). The TAPBB@GMA@AMA@Cys was successfully applied to actual sample analysis; 235 N-glycopeptides related to 125 glycoproteins and 210 N-glycopeptides related to 121 glycoproteins were recognized from the serum of normal individuals and Alzheimer’s disease patients, respectively. Gene ontology studies of molecular functions, cellular components, and biological processes have revealed that identified glycoproteins are strongly associated with neurodegenerative diseases involving innate immune responses, basement membranes, calcium binding, and receptor binding. The above results confirm the surprising potential of materials in glycoproteomics research and practical sample applications. Graphical abstract